PHARMACETUTICAL AND ECONOMICAL PROSPECTIVE OF MICROSPONGES DRUG DELIVERY SYSTEM - Mansi Gupta; Ashish Mishra (Asian Journal of Pharmaceutical Research and Development, 2025)
Microsponges are considered as one among the most proficient carrier for the delivery of Active Pharmaceutical Ingredients (API).In the recent past many articles have been published on the microsponges because of its long lasting efficacy. The uses of microsponges are basically focused on the treatments of skin ailments. Cosmeceuticals are cosmetic products with bioactive ingredients purported to have medical benefits where microsponges plays the vital role as drug delivery carrier. In the present article the focus is to highlight the pharmaceutical as well as the economical prospect of the microsponges.